Elucidating How Different Amphipathic Stabilizers Affect BSA Protein Conformational Properties and Adsorption Behavior - Ma, Gamaliel Junren (Langmuir : the ACS journal of surfaces and colloids, 2020)
Natural proteins such as bovine serum albumin (BSA) are readily extracted from biological fluids and widely used in various applications such as drug delivery and surface coatings. It is standard practice to dope BSA proteins with an amphipathic stabilizer, most commonly fatty acids, during purification steps to maintain BSA conformational properties. There have been extensive studies investigating how fatty acids and related amphiphiles affect solution-phase BSA conformational properties, while it is far less understood how amphipathic stabilizers might influence noncovalent BSA adsorption onto solid supports, which is practically relevant to form surface coatings. Herein, we systematically investigated the binding interactions between BSA proteins and different molar ratios of caprylic acid (CA), monocaprylin (MC), and methyl caprylate (ME) amphiphiles-all of which have 8-carbon-long, saturated hydrocarbon chains with distinct headgroups-and resulting effects on BSA adsorption behavior on silica surfaces. Our findings revealed that anionic CA had the greatest binding affinity to BSA, which translated into greater solution-phase conformational stability and reduced adsorption-related conformational changes along with relatively low packing densities in fabricated BSA adlayers. On the other hand, nonionic MC had moderate binding affinity to BSA and could stabilize BSA conformational properties in the solution and adsorbed states while also enabling BSA adlayers to form with higher packing densities. We discuss physicochemical factors that contribute to these performance differences, and our findings demonstrate how rational selection of amphiphile type and amount can enable control over BSA adlayer properties, which could lead to improved BSA protein-based surface coatings